2019
DOI: 10.3390/math7080741
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Control of IPMC Actuators Based on LSSVM-NARX Paradigm

Abstract: Ionic polymer-metal composites are electrically driven intelligent composites that are readily exposed to bending deformations in the presence of external electric fields. Owing to their advantages, ionicpolymer-metal composites are promising candidates for actuators. However, ionicpolymer-metal composites exhibit strong nonlinear properties, especially hysteresis characteristics, resulting in severely reduced control accuracy. This study proposes an ionic polymer-metal composite platform and investigates its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Zamyad et al [ 46 ] proposed an improved ANFIS‐NARX model that extends the input space by substituting a hysteresis operator for the previous output samples. In order to overcome the IPMC hysteresis phenomenon, Huang et al [ 47 ] used the least squares support vector machine (LSSVM) NARX model to model the tip displacement of IPMC actuators and proposed an artificial honeycomb algorithm to optimize the LSSVM NARX model's parameters. A related study has shown that there is a definite relationship between the electrical characteristics and shape of IPMCs, especially between the resistance and shape of IPMCs.…”
Section: Nonphysical Identification Modelsmentioning
confidence: 99%
“…Zamyad et al [ 46 ] proposed an improved ANFIS‐NARX model that extends the input space by substituting a hysteresis operator for the previous output samples. In order to overcome the IPMC hysteresis phenomenon, Huang et al [ 47 ] used the least squares support vector machine (LSSVM) NARX model to model the tip displacement of IPMC actuators and proposed an artificial honeycomb algorithm to optimize the LSSVM NARX model's parameters. A related study has shown that there is a definite relationship between the electrical characteristics and shape of IPMCs, especially between the resistance and shape of IPMCs.…”
Section: Nonphysical Identification Modelsmentioning
confidence: 99%
“…Among such models are the Preisach operator [81], Prandtl-Ishlinskii hysteresis models [28], [42], [43], [82], [83], and Bouc-Wen hysteresis model [27]. In [100] the least squares support vector machine nonlinear autoregressive model was developed to eliminate the effect of the hysteresis. Moreover, an inverse controller was combined with the PID feedback control to compensate the hysteretic characteristics.…”
Section: B Hysteresismentioning
confidence: 99%
“…Several researchers have tried to get an identified model of nonlinear processes for the controller implementation [4][5][6]. Many processes are nonlinear in the chemical, food, and pharmaceutical industries and have multiple operating regions over their operating range.…”
Section: Introductionmentioning
confidence: 99%